Experience of the strategy implemented by the rapid response and clinical follow-up teams to reduce COVID-19 lethality, Lambayeque-Peru 2020 - Díaz-Vélez, Cristian (2021)
Background: Peru was considered the highest fatality rate due to COVID-19 (9.39%); Lambayeque being in July 2020 it presented the highest seroprevalences reported in the world for SARS-CoV-2 with 29.5%. Objective. To describe the experience of the strategy implemented by Rapid Response and Clinical Follow-up Teams of COVID-19 Cases (ERSC) to reduce COVID-19 lethality, during the first wave in 2020. Strategy description. Operational research was conducted in a retrospective cohort. The population studied was made up of suspected and confirmed COVID-19 cases during the April-December 2020 period, treated at the Lambayeque Healthcare Network. The methodology was carried out under the Implementation and operation of the ERSCs that performed Epidemiological Surveillance, tracking and home clinical follow-up of suspected and confirmed COVID-19 cases. The initial patient recruitment and screening process was carried out through three processes: differentiated screening, "call center" and rumor surveillance. After screening, the patient was categorized based on the care required. Cases were assigned to rapid response teams who went to the patient's home to carry out the activities indicated according to the type of brigade. There were four brigades: home clinical evaluation brigades, home diagnostic or laboratory brigades, clinical follow-up brigades and mole brigades. findings. Case fatality in moderate/severe patients decreased from 60% (Epidemiological Week 19) to 10% (Epidemiological Week 50) (p<0.001). The strategy implemented and executed reduced COVID-19 case-fatality in the population served.